Explaining differences in the development of denominational schools - Rakar, Tatjana (Teorija in praksa, 2009)
The article tries to explain differences and similarities seen in the development of denominational schools in the special environment of post-socialist countries by considering state policies on denominational schools and other relevant factors such as the level of religiosity, the role of the church in public schools and the heterogeneity of the religious population. It shows that different state policies on denominational schools have on one side influenced the extent of the development of denominational schools, which is evident from the cases of Slovenia and Hungary and partly from the case of Poland but, on the other side, the case of Poland shows that we cannot explain the extent of the growth of denominational schools merely on the basis of state educational policies. Two particularly important factors for the development of denominational schools are the heterogeneity of the religious population and the character of public schools in terms of religious neutrality. The article concludes by discussing political influences on the development of denominational schools.
Keywords: Cerkvene šole; Church schools; Educational policy; Izobraževalna politika; Postsocialism; Postsocializem; Slovenia; Slovenija; Madžarska; Hungary; Poland; Poljska; postsocialistične države; politični vpliv; razvoj